On the Design of Monetary Policy Committees - Alan S. Blinder (Norges Bank, 2008)
Keynote lecture prepared for the Norges Bank research workshop "Monetary Policy Committees," Oslo, September 6-7, 2007.
hdl:11250/2497780
Keywords: 330; monetary policy committees; collective decision-making; central bank communication